2009
DOI: 10.1097/tp.0b013e3181a75917
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival of Fully Mismatched Cardiac Allografts and Generation of Regulatory Cells by Sairei-to, a Japanese Herbal Medicine

Abstract: Sairei-to (TJ114), a 12-component Japanese herbal medicine, is used to treat immune-related diseases. We investigated the effects of oral administration of TJ114 in a murine model of cardiac transplantation with fully mismatched allografts. Untreated CBA mice rejected C57BL/6 hearts acutely (median survival time [MST], 7 days), whereas survival of allografts from mice given TJ114 was significantly prolonged (MST >100 days). Secondary CBA recipients of C57BL/6 hearts also had prolonged allograft survival (MST >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Third, Tregs generated by iPS-DCregs were vital in allograft tolerance (Joffre et al., 2008, Kitazawa et al., 2007, Sakaguchi, 2004, Zhang et al., 2009b), especially in the maintenance phase (1–3 months post operation). Interestingly, donor-type iPS-DCregs served as the “primary vaccination,” which “prepared” the inhibited immune situation for the allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Tregs generated by iPS-DCregs were vital in allograft tolerance (Joffre et al., 2008, Kitazawa et al., 2007, Sakaguchi, 2004, Zhang et al., 2009b), especially in the maintenance phase (1–3 months post operation). Interestingly, donor-type iPS-DCregs served as the “primary vaccination,” which “prepared” the inhibited immune situation for the allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Active suppression by regulatory cells has been found to be one of the important mechanisms for induction and maintenance of self-tolerance [10] and unresponsiveness to allografts [11] and prevention of vasculopathy in cardiac allografts [1216]. Additionally, many manuscripts on herbal medicines we have ever submitted indicated the potential of immunomodulation and immunosuppressive effect of herbal medicines [1, 2]. Also, one recent study showed triptolide, one component of Chinese herbal medicine, facilitated the expansion of regulatory T cells via modulation of dendritic cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies of our murine model, oral administration of the Japanese herbal medicines Tokishakuyakusan (TJ-23) [1], Saireito (TJ-114) [2], or Artemisiae Capillaris Herba [3] was associated with significantly prolonged survival of allogeneic cardiac grafts (median survival times (MSTs) of all groups > 100 days) and generation of regulatory cells. Paeoniae radix ( Paeonia lactiflora ) and Cnidii rhizoma ( Cnidium officinale ) were two components of TJ-23, and, in this study, we examined whether the combination of Paeoniae radix and Cnidii rhizoma could affect the duration of allograft survival in the same model.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Weir [22] showed that Radix Tripterygium wilfordii, a Chinese herbal medicine, has immunosuppressive effects in human blood mononuclear cells in vitro. In recent studies in our murine model, oral administration of the Japanese herbal medicines Sairei-to (TJ-114) [23], Tokishakuyaku-san (TJ-23) [24], or Artemisiae Capillaris Herba [25] was associated with significantly prolonged survival of allogeneic cardiac grafts and generation of regulatory cells. In the current study, we examined whether olfactory exposure to TJ-23 affected duration of allograft survival in the same model.…”
Section: Introductionmentioning
confidence: 99%